Female workers' silicosis diagnosis delayed due to gender bias - Kerget, B.; Araz, O.; Ucar, E. Yilmazel; Karaman, A.; Calik, M.; Alper, F.; Akgun, M. (Oxford Univ Press, 2019)
After excluding alternative explanations, a silicosis diagnosis is based on the combination of appropriate silica exposure history and compatible clinical, radiological and occasionally pathological findings. Not taking appropriate occupational history by a physician may cause a misdiagnosis or underdiagnosis of silicosis. Herein, we present a female worker in a small-scale sandblasting factory who worked as a controller. Her silicosis diagnosis was established 10 years after her first symptoms, and she underwent invasive procedures due to a lack of inquiry about her occupational history. Gender bias may be one of the reasons that her occupational history was not taken.
Keywords: Female; gender bias; silicosis; underdiagnosis